Reaksi Pasar Modal Indonesia terhadap Peresmian Danantara pada Saham Perusahaan Indeks IDX BUMN20 di Bursa Efek Indonesia - Nadhea Hasna Annisa; Rousilita Suhendah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The objective of this study is to examine whether significant differences exist in abnormal returns, trading volume activity, and trading frequency of firms included in the IDX BUMN20 Index on the Indonesia Stock Exchange before and after the inauguration of Danantara. The research employs secondary data derived from IDX BUMN20 constituent firms, covering a three-day window prior to and a three-day window following the event. The sample was selected using purposive sampling, yielding a total of 20 firms. Data analysis was conducted using EViews version 12. The empirical results indicate that there are no statistically significant differences in abnormal returns, trading volume activity, or trading frequency in the periods before and after the inauguration of Danantara.